Analysis of Factors Affecting Entrepreneurial Interest of Vocational High School Students in Pekanbaru - Nurmaliza Nurmaliza; Caska Caska; Henny Indrawati (Journal of Educational Sciences, 2018)
The highest unemployment rate (TPT) in Indonesia is from graduated of Vocational High School (SMK), which is 9.27%. This phenomenon cannot be separated from the low interest of entrepreneurship. SMK graduates are expected to be able to work directly and can open employment area; the fact is far different from expectations. This study aims to analyze the factors that affect student entrepreneurship interest in SMK. The population of this study was 1845 students of class XII SMK Negeri in Pekanbaru City. The sampling method used in this research was Simple Random Sampling so that it obtained 329 students. The data collection used questionnaire with Likert scale that is suitable for exogenous variable (entrepreneurship interest), endogen variable (entrepreneurship education and family environment), and intervening variable (personality). The data analysis technique employed the path analysis method. The results of the analysis show that entrepreneurship education, and family environment have positive and significant influence on entrepreneurship interest through the personality. This shows that interest in entrepreneurship can be enhanced if the quality of entrepreneurship education, family environment and student personality are improved.